Predicting the development of liver cirrhosis by simple modelling in patients with chronic hepatitis C. Issue 3 (18th November 2015) - Lens, S.; Torres, F.; Puigvehi, M.; Mariño, Z.; Londoño, M.‐C.; Martinez, S. M.; García‐Juárez, I.; García‐Criado, Á.; Gilabert, R.; Bru, C.; Solà, R.; Sanchez‐Tapias, J. M.; et al.
Summary: Background: Data are scarce on the natural history of chronic hepatitis C (CHC) in patients with mild hepatitis C who did not respond to anti‐viral therapy. Aim: To predict the risk of progression to cirrhosis, identifying patients with the more urgent need for therapy with effective anti‐virals. Methods: A cohort of 1289 noncirrhotic CHC patients treated with interferon‐based therapy between 1990 and 2004 in two referral hospitals were followed up for a median of 12 years. Results: Overall, SVR was achieved in 46.6% of patients. Data from a randomly split sample ( n = 832) was used to estimate a model to predict outcomes. Among nonresponders ( n = 444), cirrhosis developed in 123 (28%) patients. In this group, the 3, 5 and 10‐year cumulative probabilities of cirrhosis were 4%, 7% and 22%, respectively, compared to <1% in the SVR‐group ( P < 0.05). Baseline factors independently associated with progression to cirrhosis in nonresponders were: fibrosis ≥F2, age >40 years, AST >100 IU/L, GGT >40 IU/L. Three logistic regression models that combined these simple variables were highly accurate in predicting the individual risk of developing cirrhosis with areas under the receiving operating characteristic curves (AUC) at 5, 7 and 10 years of ~0.80. The reproducibility of the models in the validation cohort ( n = 457, nonresponders = 244), was consistently high. Conclusions: Modelling based on simple laboratory and clinical data can accurately identify the individual risk of progression to cirrhosis in nonresponder patients with chronic hepatitis C, becoming a very helpful tool to prioritise the start of oral anti‐viral therapy in clinical practice.